Suaeda glauca adsorbing material as well as preparation method and application thereof

By modifying citric acid and ethyl acetate on the alkaline cypermia, a alkaline cypermia adsorption material with high adsorption capacity was prepared, which solved the problems of alkaline cypermia resource utilization and formaldehyde adsorption, and achieved efficient and low-cost formaldehyde Removal effect.

CN119258996APending Publication Date: 2025-01-07YUNCHENG UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411560502.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize the resources of Alkaliensis, resulting in waste and environmental pollution. At the same time, the adsorption effect of formaldehyde is poor and the lack of efficient and low-cost biosorbents.

Method used

By placing the alkaline saccharide in citric acid and ethyl acetate solution for modification, soluble cellulose and protein were removed, and insoluble cellulose and hemicellulose reticular structure was retained to prepare alkaline saccharide adsorption with loose porous structures. Material.

Benefits of technology

It improves the adsorption capacity of the Alkalifos adsorbent material, achieves excellent formaldehyde removal effect, is low cost and cost-effective, and provides a feasible biosorbent solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258996A_ABST
    Figure CN119258996A_ABST
Patent Text Reader

Abstract

The invention discloses a suaeda glauca adsorbing material as well as a preparation method and application thereof, and belongs to the field of air purification. The suaeda glauca adsorption material for removing formaldehyde is obtained by modifying suaeda glauca with ethyl acetate and citric acid, and compared with adsorption materials such as activated carbon, kieselguhr and resin in the prior art, the suaeda glauca adsorption material has a more excellent adsorption effect on removing formaldehyde, is economical and environmentally friendly and has excellent industrial prospects; and the preparation method of the suaeda glauca adsorption material is simple and easy to implement, the production cost is low, and large-scale production can be carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of air purification, and particularly relates to a Suaeda salsa adsorption material and a preparation method and application thereof. Background Art

[0002] Formaldehyde is a colorless toxic gas that is suffocating, easily soluble in water, alcohols and other polar solvents, and seriously endangers human health. Formaldehyde is highly irritating to biological mucous membranes and has a tear-inducing effect. It can coagulate proteins and easily cause skin hardening or even local tissue necrosis when it touches the skin. The gas is often masked by other odors at low concentrations, and has a strong irritating and suffocating odor at high concentrations. Long-term exposure to an environment with high formaldehyde concentrations can cause dizziness, headaches, tears, nausea and vomiting, coughing, chest tightness, leukemia, and other serious conditions can lead to death. The gas appears more in furniture and decoration materials that do not meet quality standards. Formaldehyde (CH2O) is the simplest aldehyde and is usually classified as a saturated monoaldehyde. In organic solvents, formaldehyde can undergo catalytic addition reactions with monoolefins to generate dienes or corresponding alcohols. It has reducing properties, especially in alkaline solutions, where the reducing ability is stronger. It can burn vapor and form an explosive mixture with air, with an explosion limit of 7% to 73% (volume percentage) and a flash point of about 300°C. Formaldehyde can be used directly as a disinfectant, sterilizer, and preservative. A 35% to 40% formaldehyde aqueous solution is commonly known as formalin. In industry, formaldehyde is mainly used in the form of aqueous solution, polymers, and various derivatives. It is widely used in petrochemical, pharmaceutical, textile, biochemical, energy, transportation and other industries. It can be used as a disinfectant and preservative, and can also be used to prepare phenolic resin, urea-formaldehyde resin, melamine resin, hexamethylenetetramine, pentaerythritol and other products. Since formaldehyde can undergo a variety of reactions, they are generally not indicated one by one. On October 27, 2017, the World Health Organization (WHO) announced that formaldehyde is a Class 1 carcinogen.

[0003] Suaeda heteroptera Kitog is an annual Chenopodiaceae plant that grows in saline-alkali areas. It is rich in nutrients and is a high-quality vegetable and oil crop. Suaeda heteroptera Kitog is often used as agricultural tourism and garden landscape in garden landscapes. Suaeda heteroptera Kitog contains vitamins, minerals, carbohydrates, high organic iron and high organic selenium required by the human body. It also has extraordinary medicinal effects. Regular consumption can lower blood sugar and blood pressure, prevent and treat heart disease and enhance human immunity. However, most Suaeda heteroptera Kitog is not used reasonably or eventually withers and is treated as garbage, or even burned, resulting in a waste of biological resources, affecting environmental hygiene and causing air pollution.

[0004] Domestic research status and development trends on formaldehyde: China has paid great attention and importance to the problem of purifying the air environment and adsorbing formaldehyde, which has become a hot topic for many scholars and has achieved many research results. For example, most studies have achieved a large number of results in the field of preparing various formaldehyde adsorbents, mainly using activated carbon and other adsorbents to adsorb formaldehyde, using green plants to absorb formaldehyde, plasma oxidation to degrade formaldehyde, photocatalytic oxidation of formaldehyde, ozone oxidation to decompose formaldehyde, catalytic oxidation of formaldehyde at room temperature, and amino acid cellulose to absorb formaldehyde. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a Suaeda salsa grass adsorption material and a preparation method and application thereof, which solves the problem of Suaeda salsa grass waste and modifies it into a biosorbent.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a Suaeda salsa adsorption material, comprising the following steps:

[0007] S1: Soak the Suaeda salsa in a 0.4-0.6 mol / L citric acid solution for 150-200 min;

[0008] S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.1-0.5 mol / L ethyl acetate solution for 24 hours to obtain a crude product;

[0009] S3: The crude product is rinsed to neutrality, and then dried and crushed to obtain the Suaeda salsa adsorption material.

[0010] The beneficial effects of the present invention are as follows: the present invention removes soluble cellulose and protein in the Suaeda salsa by modifying the Suaeda salsa with ethyl acetate and citric acid, retains a large amount of dense insoluble cellulose and hemicellulose network structure, makes the Suaeda salsa present a loose and porous form, greatly enhances the adsorption capacity, and finally obtains a biosorbent with excellent adsorption effect, the preparation process is simple and easy, the production cost is low, and has excellent industrial prospects.

[0011] Based on the above technical solution, the present invention can also be improved as follows.

[0012] Furthermore, the concentration of the citric acid solution was 0.55 mol / L, and the soaking time was 190 min.

[0013] Furthermore, the concentration of the ethyl acetate solution was 0.4 mol / L.

[0014] The beneficial effect of adopting the further technical solution is: the preferred solution enables the obtained Suaeda salsa adsorption material to have better technical effect.

[0015] Furthermore, the drying treatment is carried out in an oven at 65-75° C. for 1 day.

[0016] The invention also discloses a method for preparing the Suaeda salsa grass adsorption material and a Suaeda salsa grass adsorption material obtained by the method.

[0017] Furthermore, the particle size of the Suaeda salsa adsorption material is 60 meshes.

[0018] The invention also discloses the application of the Suaeda salsa adsorption material in removing formaldehyde.

[0019] The beneficial effect of the present invention is that a large amount of discarded Suaeda salsa is modified by ethyl acetate and citric acid and then used to remove formaldehyde. Compared with activated carbon, diatomaceous earth and other materials in the prior art, the Suaeda salsa adsorption material provided by the present invention has better adsorption effect and lower price, making it more cost-effective in competition with the products in the prior art and making the biosorbent more promising. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a statistical diagram of the effect of removing formaldehyde by the Suaeda salsa adsorption material prepared in Examples 1 to 5;

[0021] Figure 2 The effect of ethyl acetate concentration and citric acid soaking time on the removal rate;

[0022] Figure 3 This is a statistical diagram of the effect of the particle size of the slag of the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2 on the removal of formaldehyde;

[0023] Figure 4 This is a statistical chart showing the effect of the amount of Suaeda salsa adsorption material added on the removal of formaldehyde obtained under the optimized conditions of Experimental Example 2;

[0024] Figure 5 This is a statistical chart of the effect of temperature on formaldehyde removal;

[0025] Figure 6 This is a statistical chart showing the effect of adsorption time on formaldehyde removal;

[0026] Figure 7 This is a statistical chart of the effect of initial formaldehyde concentration on formaldehyde removal;

[0027] Figure 8 is the relationship between the initial concentration of formaldehyde and the adsorption amount;

[0028] Fig. 9 Langmuir model of formaldehyde removal by Suaeda salsa adsorption material prepared under optimized conditions in Experimental Example 2;

[0029] Fig.10 The Freundich model of formaldehyde removal by the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2;

[0030] Fig.11 It is a single factor change diagram over time;

[0031] Fig.12 The pseudo-first-order adsorption kinetic curves of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 at different times;

[0032] Fig.13 The quasi-secondary adsorption kinetic curves of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 at different times;

[0033] Fig.14 This is a thermodynamic analysis equation diagram of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2;

[0034] Fig.15 This is the SEM image of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2;

[0035] Fig.16 This is the SEM image of the original Suaeda salsa;

[0036] Fig.17 is the infrared spectrum;

[0037] Fig.18 This is a comparison chart of the effects of 6 adsorption materials on formaldehyde removal;

[0038] Fig.19 This is the desorption recovery analysis diagram of the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2. DETAILED DESCRIPTION

[0039] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0040] Example 1

[0041] A method for preparing a Suaeda salsa adsorption material comprises the following steps:

[0042] S1: Soak Suaeda salsa in 0.5 mol / L citric acid for 180 min;

[0043] S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.1 mol / L ethyl acetate for 24 hours to obtain a crude product;

[0044] S3: The crude product was rinsed to neutrality, then dried in an oven at 70°C for 1 day, and then crushed into 60-mesh particles to obtain the Suaeda salsa adsorption material.

[0045] Example 2

[0046] A method for preparing a Suaeda salsa adsorption material comprises the following steps:

[0047] S1: Soak Suaeda salsa in 0.4 mol / L citric acid for 150 min;

[0048] S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.2 mol / L ethyl acetate for 24 hours to obtain a crude product;

[0049] S3: The crude product was rinsed to neutrality, then dried in an oven at 65°C for 1 day, and then crushed into 60-mesh particles to obtain the Suaeda salsa adsorption material.

[0050] Example 3

[0051] A method for preparing a Suaeda salsa adsorption material comprises the following steps:

[0052] S1: Soak Suaeda salsa in 0.6 mol / L citric acid for 200 min;

[0053] S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.3 mol / L ethyl acetate for 24 hours to obtain a crude product;

[0054] S3: The crude product was rinsed to neutrality, then dried in an oven at 75°C for 1 day, and then crushed into 60-mesh particles to obtain the Suaeda salsa adsorption material.

[0055] Example 4

[0056] A method for preparing a Suaeda salsa adsorption material comprises the following steps:

[0057] S1: Soak Suaeda salsa in 0.55 mol / L citric acid for 190 min;

[0058] S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.4 mol / L ethyl acetate for 24 hours to obtain a crude product;

[0059] S3: The crude product was rinsed to neutrality, then dried in an oven at 70°C for 1 day, and then crushed into 60-mesh particles to obtain the Suaeda salsa adsorption material.

[0060] Example 5

[0061] A method for preparing a Suaeda salsa adsorption material comprises the following steps:

[0062] S1: Soak Suaeda salsa in 0.5 mol / L citric acid for 180 min;

[0063] S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.5 mol / L ethyl acetate for 24 hours to obtain a crude product;

[0064] S3: The crude product was rinsed to neutrality, then dried in an oven at 70°C for 1 day, and then crushed into 60-mesh particles to obtain the Suaeda salsa adsorption material.

[0065] Experimental Example 1

[0066] Formaldehyde adsorption experiment: The formaldehyde detector was placed in 5 plastic wrap sealed boxes with a length, width and height of 40 cm respectively, and a fixed position was marked in each box for placing the Suaeda salsa adsorption material, and the diluted formaldehyde solution was used as the source of formaldehyde gas to simulate an indoor air environment with excessive formaldehyde. When the gas in the box diffused evenly and the formaldehyde concentration was stable, the formaldehyde solution was taken out, and then 1g of the Suaeda salsa adsorption material prepared in Examples 1 to 5 was placed in each of the 5 boxes, and the formaldehyde concentration in the box was tested again after 30 minutes.

[0067] The calculation formula of the removal rate N of Suaeda salsa adsorption material is:

[0068] N=(n1-n2) / (n1-N0)×100%,

[0069] Where n1 is the initial reading of the formaldehyde detector, n2 is the reading of the formaldehyde detector after the estimated removal time, and N0 is the empty box leakage rate;

[0070] The calculation formula for the empty box leakage rate N0 is:

[0071] N0=(n0-n) / n0,

[0072] Among them, n0 is the fixed value reached by the formaldehyde detector, and n is the reading of the formaldehyde detector without adding the Suaeda salsa adsorption material but after the expected removal time.

[0073] The experimental results are as follows Figure 1 As shown, when the ethyl acetate concentration is 0.4 mol / L (Example 4), the removal rate reaches a peak value of 19%, and the adsorption effect is good; the adsorption amount gradually increases and then slightly decreases as the ethyl acetate concentration continues to increase, and the maximum adsorption amount is 0.044 mg / g.

[0074] Experimental Example 2

[0075] Optimization experiment: The treatment method of the alkali grass adsorption material was optimized by using a quadratic orthogonal rotation regression combined experimental design. The experimental data were analyzed using DPS software, and the ethyl acetate concentration, citric acid concentration and soaking time in citric acid were selected as the key factors affecting the removal rate of the alkali grass adsorption material. The factor level coding table was compiled as shown in Table 1, and then a quadratic orthogonal rotation regression combined experimental design table was drawn based on Table 1, as shown in Table 2. The alkali grass adsorption material was optimized and prepared according to the technical parameters in Table 2.

[0076] Table 1 Factor level coding table

[0077]

[0078] Table 2 Quadratic orthogonal rotation regression combination experimental design table

[0079]

[0080]

[0081] After the removal rate of the optimized Suaeda salsa adsorption material prepared according to Table 2 was measured by the method of Experimental Example 1, a variance analysis was performed on the removal rate. The results are shown in Table 3 (ethyl acetate concentration X1, citric acid concentration X2, citric acid soaking time X3).

[0082] Table 3 ANOVA table

[0083] Sources of variation Sum of Squares (SS) Degrees of freedom (df) Mean square (MS) Ratio F P-value <![CDATA[X1]]> 2.5086 1 2.5086 8.004 0.0142 <![CDATA[X2]]> 2.969 1 2.969 9.473 0.0088 <![CDATA[X3]]> 0.0651 1 0.0651 0.2076 0.6561 <![CDATA[X1 2 ]]> 0.0478 1 0.0478 0.1526 0.7023 <![CDATA[X2 2 ]]> 5.3119 1 5.3119 16.9481 0.0012 <![CDATA[X3 2 ]]> 0.0001 1 0.0001 0.0001 0.9983 <![CDATA[X1X2]]> 0.0113 1 0.0113 0.0359 0.8527 <![CDATA[X1X3]]> 1.3448 1 1.3448 4.2907 0.0588 <![CDATA[X2X3]]> 0.0128 1 0.0128 0.0408 0.843 return 12.2787 9 1.3643 <![CDATA[F2=4.353]]> 0.0165 Remaining 4.0744 13 0.3134 Lack of Fit 2.7879 5 0.5576 <![CDATA[F1=3.467]]> 0.0328 error 1.2866 8 0.1608 sum 1.63532 22

[0084] According to the DPS software analysis, the following model regression equation is obtained: Y = 18.33429 + 0.42859X1 + 0.46626X2 + 0.06903X3 + 0.05887X1 2 +0.57859X2 2 +0.00407X3 2 +0.03750X1X2+0.41000X1X3+0.04000X2X3.

[0085] From Table 3, we can see that at the level of α = 0.01, F 失拟 =3.467 <F 0.01(5,8) =6.63, indicating that the experimental error is very small and all unknown factors have been taken into account in the experimental design; F 回归 =4.353>F 0.01(9,13) =4.19, indicating that the regression equation has reached an extremely significant level, the experimental speculation is extremely reliable, and the prediction accuracy model is established.

[0086] Through a variance analysis (Table 3), it can be concluded that X2 2 The difference is extremely significant at the 0.01 level, and the differences among X1, X2, and X1X3 are significant at the 0.05 level. Since the design is orthogonal, there is no correlation between the regression coefficients. At the α=0.10 level, the insignificant items can be eliminated, and the simplified regression equation formed by quadratic analysis of variance (Table 4) is: Y=18.33429+0.42859X1+0.46626X2+0.57859X2 2 +0.41000X1X3

[0087] Table 4 Quadratic ANOVA table

[0088] Sources of variation Sum of Squares (SS) Degrees of freedom (df) Mean square (MS) Ratio F P-value <![CDATA[X1]]> 2.5086 1 2.5086 8.004 0.0142 <![CDATA[X2]]> 2.969 1 2.969 9.473 0.0088 <![CDATA[X2 2 ]]> 5.3119 1 5.3119 16.9481 0.0012 <![CDATA[X1X3]]> 1.3448 1 1.3448 4.2907 0.0588 return 12.2787 9 1.3643 <![CDATA[F2=4.353]]> 0.0165 Remaining 4.0744 13 0.3134 sum 16.3532 22

[0089] From the ANOVA table, it can be seen that the interactions between the three factors (X1, X2, and X3) will affect the adsorption effect. Compared with the interactions between X1X2 and X2X3, the X1X3 interaction is significant, that is, the effect of ethyl acetate concentration and citric acid soaking time on the adsorption effect is significant. The effect of the interaction between X1X3 is shown in Table 5. The 3D diagram of the interaction relationship between X1X3 is shown in Table 5. Figure 2 .

[0090] Table 5 Effect of ethyl acetate concentration and immersion time in citric acid on removal effect

[0091]

[0092]

[0093] Under the same citric acid concentration, the removal rate of the alkali grass adsorption material increased with the extension of the soaking time; the removal rate of the alkali grass adsorption material increased with the increase of the ethyl acetate concentration while keeping the soaking time unchanged. In summary, the maximum removal rate was 22.64% when soaking for 190 minutes with 0.45 mol / L ethyl acetate and 0.55 mol / L citric acid.

[0094] Experimental Example 3

[0095] Single factor experiment: This experiment explored the formaldehyde removal effect of Suaeda salsa adsorption material based on five factors: particle size, addition amount, adsorption temperature, initial concentration of pollutants, and adsorption time.

[0096] 1. Particle size test: The 5 kinds of Suaeda salsa adsorption materials prepared under the optimized conditions of Experimental Example 2 were sieved through 18 mesh, 40 mesh, 60 mesh, 80 mesh and 100 mesh sieves respectively, and the 5 kinds of Suaeda salsa adsorption materials were used as the particle size gradient for the test: 1g of each of the 5 kinds of Suaeda salsa adsorption materials was taken, and the formaldehyde concentration in the closed box was uniformly set to 1.87mg / m 3 , adsorption time 30min, each gradient was carried out three times, and the average removal rate of the five particle sizes of Suaeda salsa adsorption materials was calculated respectively. Figure 3 As shown in the figure, as the particle size increases, the removal rate increases first and then decreases, reaching the minimum at 18 mesh and the peak at 60 mesh, that is, the 60-mesh Suaeda adsorption material has the best adsorption effect. Through analysis, it can be seen that different mesh Suaeda adsorption materials have different effects on the adsorption effect, among which the 60-mesh Suaeda adsorption material shows a very significant level, through a single variance analysis (F=2694.7650, P<0.01). Therefore, the particle size of the Suaeda adsorption material in this experiment is set to 60 mesh.

[0097] 2. Test of adsorption material addition: The 60-mesh particle size Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 was selected, and 1g, 1.5g, 2g, 2.5g and 3g of 5 gradients of Suaeda salsa adsorption material were weighed. The formaldehyde concentration in the closed box was uniformly set to 1.87mg / m 3 , adsorption time 30min, each gradient experiment was carried out, and the removal rates of 5 kinds of Suaeda salsa adsorption materials were calculated respectively. Figure 4 As shown in the figure, the removal rate increases with the increasing amount of alkali grass adsorption material, so the greater the amount of alkali grass adsorption material, the higher the removal rate, and the removal rate increases in a positive direction with the amount added. Through analysis, it can be seen that different addition amounts have different effects on the adsorption effect, among which the removal rate of 3g addition amount shows a very significant level. Through a variance analysis (F=1304.477, P<0.01), the experiment shows that adding 3g of alkali grass adsorption material has the best adsorption effect.

[0098] 3. Adsorption temperature test: Five different indoor temperatures were selected as adsorption temperatures, and a total of five gradients were used for adsorption tests. 1g of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 was taken, and the formaldehyde concentration in the closed box was uniformly set to 1.87mg / m 3 , adsorption time 30min, each gradient experiment was carried out, and the average formaldehyde removal rate at the corresponding adsorption temperature was calculated. Figure 5 As shown, when the adsorption temperature is 26℃, the removal rate reaches the peak and the adsorption effect is the best. The removal rate will decrease when it is lower or higher than 26℃. Through a variance analysis (F=502.262, P<0.01), the effect of the adsorption temperature of 26℃ on the formaldehyde adsorption effect is extremely significant. Therefore, the optimal adsorption temperature is set at 26℃.

[0099] IV. Adsorption time test: Five different adsorption times and five gradients were selected for adsorption test. 1g of Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 was taken, and the formaldehyde concentration in the closed box was uniformly set to 1.87mg / m 3 , the experiment was carried out at each gradient at room temperature, and the average formaldehyde removal rate at each adsorption time was calculated. Figure 6 As shown in the figure, as the adsorption time increases, the removal rate gradually increases, the removal rate is the smallest at 30 minutes, and the removal rate reaches a peak at 120 minutes, that is, the adsorption effect of 120 minutes is the best. Through a variance analysis (F=600.43, P<0.01), the optimal adsorption time is 120 minutes.

[0100] 5. Test on the influence of initial formaldehyde concentration: 5 different initial formaldehyde concentrations were selected for adsorption experiments. 1g of Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 was taken. At the same temperature, adsorption began when the formaldehyde concentration in the sealed box reached the set value. Each concentration gradient was adsorbed for 30 minutes, and the average formaldehyde removal rate at the corresponding adsorption temperature was calculated. The experimental results are shown in the figure. Figure 7 As shown, the initial concentration of pollutants is 1.74 mg / m 3 When the removal rate reaches the peak value, the adsorption effect is the best, which is lower or higher than 1.74 mg / m 3 The removal rate will be reduced. Through a variance analysis (F=1809.356, P<0.01), the optimal initial formaldehyde concentration is 1.74 mg / m 3 .

[0101] Experimental Example 4

[0102] Adsorption isotherm experiment: This experiment uses the Langmuir isotherm and Freundlich isotherm to describe the relationship between the Suaeda salsa adsorption material and the initial formaldehyde concentration.

[0103] The Langmuir isotherm is:

[0104] C / Q=C / Q m +1 / Q m b,

[0105] The Freundlich isotherm is:

[0106] Q=K×C n ,

[0107] Taking the logarithm of both sides of the Freundlich isotherm can be converted into a linear form:

[0108] IgK+(1 / n)IgC=IgQ

[0109] Where C is the equilibrium concentration (mg / L), Q is the equilibrium adsorption amount (mg / g), and Q m is the saturated adsorption capacity (mg / g), b is the adsorption equilibrium constant, and K and n are constants at a certain temperature.

[0110] The equilibrium adsorption amount calculation formula is:

[0111] Q=(C0-C)V / m,

[0112] Where C0 is the initial concentration (mg / m 3) ; V is the volume of the closed box (m 3) ; m is the mass of adsorbent (g).

[0113] Take 5 sealed boxes with a length, width and height of 40 cm each. At the same time and room temperature, the boxes are numbered A, B, C, D and E. The formaldehyde in the boxes comes from the formaldehyde dilution solution in the culture dish. After a certain period of evaporation, when the formaldehyde concentration rises to the predetermined concentration (1.7 mg / m 3 , 1.72mg / m 3 , 1.74mg / m 3 , 1.76mg / m 3 , 1.78mg / m 3 ), immediately remove the pollution source, and then take the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2 (1 g evenly spread in the culture dish) and put it in. After a countdown of 30 minutes, take it out, read the formaldehyde concentration value displayed on the formaldehyde detection instrument, calculate the equilibrium adsorption amount, and then fit it with the above two adsorption isotherm models.

[0114] The relationship between the initial formaldehyde concentration and the adsorption amount is as follows: Figure 8 As shown, the Langmuir model is Fig. 9 As shown, the Freundlich model is Fig.10 As shown, according to the adsorption isotherm model parameter table (Table 6), in the Freundlich model, the correlation coefficient R 2 It is closer to 1, that is, it is more inclined to the Freundlich isotherm adsorption model, indicating that the surface of the Suaeda salsa adsorption material has many active sites, and the adsorption mode is mainly a combination of multi-molecular layer physicochemical adsorption. It can be judged that after the Suaeda salsa was modified with ethyl acetate + citric acid, the number of effective functional groups on its surface increased, which improved the adsorption effect of formaldehyde.

[0115] Table 6 Adsorption isotherm model parameters

[0116]

[0117] Experimental Example 5

[0118] Adsorption kinetics experiment: When the initial concentration is the same, the adsorption effect of Suaeda salsa adsorption material on formaldehyde under five time gradients is fitted using pseudo-first-order kinetics and pseudo-second-order kinetics models.

[0119] Take a sealed box with a length, width and height of 40 cm, put a petri dish containing formaldehyde dilution in the box at room temperature at the same time, and let it evaporate for a certain period of time. When the formaldehyde concentration in the box rises to 1.87 mg / m 3 Take out the formaldehyde dilution solution, and immediately put 1g of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 into the box (evenly spread in the culture dish), and the adsorption time is 0.5h, 1h, 1.5h, 2h, 2.5h. Calculate the adsorption amount, draw the adsorption kinetic curve, and fit it with the pseudo-first-order and pseudo-second-order kinetic equations.

[0120] The pseudo-first-order dynamic equation is expressed as:

[0121] Ig(Qq)=IgQ-k1t / 2.303,

[0122] The pseudo-second-order dynamic equation is expressed as:

[0123] t / q=1 / (k2×Q)+t / Q,

[0124] Q is the equilibrium adsorption amount (mg / g), q is the adsorption amount at adsorption time t (mg / g), k1 is the first-order adsorption rate constant (g·mg -1 ·min -1 ), k2 is the secondary adsorption rate constant (g·mg -1 ·min -1 ).

[0125] The experimental results are as follows Figures 11 to 13 As shown, Fig.11 The effect of different adsorption time on the adsorption of formaldehyde is plotted on this basis with the horizontal and vertical coordinates t and Ig(Qq) to obtain the quasi-first-order adsorption kinetic curve ( Fig.12 ), and then plotting the quasi-secondary adsorption kinetic curve with the horizontal and vertical coordinates t and (t / q) ( Fig.13 ), and thus the adsorption dynamic parameter table (Table 7) was obtained. The equilibrium adsorption amount Q calculated by the pseudo-second-order equation was close to the measured value Q0, and the correlation coefficient R 2 It is also closer to 1. This indicates that the modified Suaeda salsa follows the pseudo-second-order kinetic model more and the adsorption process is mainly chemical adsorption.

[0126] Table 7 Adsorption dynamic parameters

[0127]

[0128] Experimental Example 6

[0129] Adsorption heat experiment: Thermodynamic analysis was performed on the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2. The calculation formula for adsorption heat is:

[0130] InK c =-ΔG0 / RT=-ΔH0 / RT+ΔS0 / R,

[0131] K c = =ρ1 / ρ2,

[0132] Among them, △G0 refers to the standard Gibbs free energy, the unit is kJ / mol; R refers to the thermodynamic gas constant, the value is 8.314J / (mol·K); T is the thermodynamic temperature, the unit is K; △H0 is the enthalpy variable of the reaction, the unit is kJ / mol; △S0 is the entropy variable, the unit is J / (mol·K); K Cis the thermodynamic equilibrium constant; ρ1 is the molecular mass concentration of formaldehyde gas adsorbed on the adsorbent, in mg / m 3 .

[0133] Take a sealed box with a length, width and height of 40 cm, and put a petri dish containing formaldehyde dilution in the box to allow it to evaporate for a certain period of time. When the formaldehyde concentration in the box rises to 1.87 mg / m 3 Take out the formaldehyde dilution solution and immediately put 1g of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2 into the box (evenly spread in the culture dish). The adsorption temperature was set at 22℃, 24℃, 26℃, 28℃, and 30℃ respectively to calculate the adsorption amount. The experimental results are shown in Fig.14 As shown in Table 8, ΔH0>0 and ΔG0<0, which means that the adsorption of formaldehyde by Suaeda salsa is a spontaneous endothermic process. Fig.14 It can be seen that the correlation coefficient of the fitted thermodynamic curve R 2 It is close to 1, which fits well with the thermodynamic equation, indicating that the adsorption of formaldehyde by Suaeda salsa adsorption material follows the thermodynamic law.

[0134] Table 8 Thermodynamic parameters

[0135] T / K <![CDATA[ΔG0(KJ / mol)]]> <![CDATA[ΔH0(KJ / mol)]]> <![CDATA[ΔS0(J·mol -1 ·K -1 )]]> 295 -7.114 0.257 35.789 297 -7.501 0.257 35.789 299 -7.676 0.257 35.789 301 -8.015 0.257 35.789 303 -8.278 0.257 35.789

[0136] Experimental Example 7

[0137] SEM characterization and analysis experiment: The morphology of the original Suaeda salsa and the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2 was analyzed using a scanning electron microscope. The experimental results are as follows: Figures 15-16 As shown, Fig.15 The interior of the original Suaeda salsa is basically entirely cellulose. Fig.16 The modified Suaeda salsa adsorption material removes soluble cellulose and protein, retains a large amount of dense insoluble cellulose and hemicellulose network structure, presents a loose and porous form, and greatly enhances the adsorption capacity.

[0138] Experimental Example 8

[0139] FTIR analysis experiment: Fourier transform infrared spectroscopy was used to analyze the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2, the original Suaeda salsa and the Suaeda salsa adsorption material after formaldehyde removal. The experimental results are as follows: Fig.17 As shown, A is the untreated original Suaeda salsa, and B is the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2, which is the Suaeda salsa adsorption material after formaldehyde is removed. Infrared spectroscopy shows that there are many groups in Suaeda salsa, 1500cm -1 ~600cm -1 There are many peaks in the double bond stretching vibration area. The figure shows that the hydroxyl group increases significantly after the optimal modification, and the peak is the largest; 3500cm -1The hydroxyl content changes significantly, proving that the hydroxyl content changes after the Suaeda salsa adsorption material adsorbs formaldehyde, which plays a great role in the adsorption.

[0140] Experimental Example 9

[0141] Element analysis: The element analysis of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2, the original Suaeda salsa and the Suaeda salsa adsorption material after formaldehyde removal was performed. The experimental results are shown in Table 9. The original Suaeda salsa contains a large amount of C and H elements, among which the S element has the least content. It can be found from the table that the content of C and H elements increases significantly after ethyl acetate + citric acid treatment, and other elements also increase slightly. After adsorption, the N element tends to decrease, because the N element reacts with formaldehyde to reduce. Therefore, the Suaeda salsa adsorption material has a better formaldehyde adsorption effect.

[0142] Table 9 Elemental analysis table

[0143]

[0144] Experimental Example 10

[0145] BET analysis: Specific surface area and pore size analyzer were used to detect the specific surface area and pore size of the Suaeda salsa adsorption material obtained under the optimized conditions of Experimental Example 2, and the physical structure of the adsorption of the Suaeda salsa adsorption material was explored. The experimental results are shown in Table 10. The specific surface area of ​​the Suaeda salsa adsorption material is large, indicating that the Suaeda salsa adsorption material is a highly active porous material with porous gaps and strong adsorption capacity.

[0146] Table 10 Specific surface area and pore size analysis

[0147] Test items Suaeda salsa adsorption material <![CDATA[Specific surface area (m 2 / g)]]> 2.074 <![CDATA[Pore volume (cm 3 / g)]]> 0.004 Pore ​​size distribution (d) 3.068

[0148] Experimental Example 11

[0149] Horizontal comparison experiment: Take the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2 and conduct adsorption tests with diatomaceous earth, activated carbon, bamboo charcoal, resin and original Suaeda salsa. Take 1g of each adsorption material, set the adsorption time gradient to 30min, 60min, 90min, 120min, 150min. Set the same formaldehyde concentration for each adsorption material to carry out the experiment, calculate its actual removal rate, and compare the adsorption effect.

[0150] The experimental results are as follows Fig.18 As shown in the figure, the adsorption effect of modified Suaeda salsa (Suaeda salsa adsorption material) is more prominent than the other five. Different adsorption materials will have a significant impact on the adsorption effect. There is also an interaction between the material and time, which affects the adsorption effect. From the first-order variance, we can see that (F 材料=4213.381, P<0.01). Among the six adsorption materials, the modified Suaeda salsa (Suaeda salsa adsorption material) had an extremely outstanding adsorption effect, which was significantly higher than the other five adsorption materials.

[0151] Experimental Example 12

[0152] Desorption and recovery experiment: Weigh 1g of the Suaeda salsa adsorption material prepared under the optimized conditions of Experimental Example 2, conduct an adsorption test in a closed box with 1.87mg / L formaldehyde, and calculate its removal rate. Add 0.1mol / L hydrochloric acid to the Suaeda salsa adsorption material after adsorption, and the desorption process is 3h. After filtering with filter paper, wash with distilled water to neutrality, dry at 70℃, repeat the above test process, and test repeatedly 7 times to explore the changes in adsorption performance.

[0153] The experimental results are as follows Fig.19 As shown in the figure, with the increase of desorption times, the removal rate of the Suaeda salsa adsorption material gradually decreased, but the decline was small. The removal rate at the 7th desorption was 22.46%, which still had a good adsorption effect. This shows that the Suaeda salsa adsorption material can be desorbed and then adsorbed, and the adsorption effect after desorption is very good, and it can be recycled more than 7 times. Through variance analysis, it can be seen (F=123.43, P<0.01), there is a significant difference.

[0154] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing a Suaeda salsa adsorption material, characterized in that: The following steps are involved: S1: Soak the Suaeda salsa in a 0.4-0.6 mol / L citric acid solution for 150-200 min; S2: Rinse the alkali grass soaked in citric acid until it is neutral, and soak it in 0.1-0.5 mol / L ethyl acetate solution for 24 hours to obtain a crude product; S3: The crude product is rinsed to neutrality, and then dried and crushed to obtain the Suaeda salsa adsorption material.

2. A method for preparing a Suaeda salsa adsorption material, characterized in that: The concentration of the citric acid solution is 0.55 mol / L, and the soaking time is 190 min.

3. A method for preparing a Suaeda salsa adsorption material, characterized in that: The concentration of the ethyl acetate solution is 0.4 mol / L.

4. The method for preparing the Suaeda salsa adsorption material according to claim 1, characterized in that: The drying is carried out in an oven at 65-75° C. for 1 day.

5. The Suaeda salsa grass adsorption material obtained by the method for preparing the Suaeda salsa grass adsorption material according to any one of claims 1 to 4.

6. The Suaeda salsa adsorption material according to claim 5, characterized in that: The particle size of the Suaeda salsa adsorption material is 60 meshes.

7. Use of the Suaeda salsa adsorption material according to claim 5 or 6 in removing formaldehyde.

Citation Information

Cited By

  • Halophyte-based adsorbent preparation process and device thereof

    CN120771835A